Reorientating Taiwan: Ocean, Selfhood, and the Pacific - Alsford, Niki J.P.; Chang, Ti-han (Asian Studies E-Books Online, Collection 2026., 2025)
Reorientating Taiwan: Ocean, Selfhod, and the Pacific redefines how you see Taiwan, moving beyond land-centred perspectives to embrace its deep connection with the Pacific. This interdisciplinary collection takes you on a journey through anthropology, literature, ecology, and art, revealing Taiwan as a cradle of Austronesian expansion and a hub of oceanic entanglements. You'll discover how Taiwan's vibrant marine culture influences its identity, from Indigenous traditions to contemporary environmental activism. This book invites you to explore Taiwan's cultural and ecological narratives in a way that is both profound and transformative.